Clinical guidelines and expediency of using 5-aminolevulinic acid for intraoperative visualization of margins of malignant tumors of the oral cavity - Yu. V. Alymov; A. V. Ignatova; I. S. Romanov (Опухоли головы и шеи)
Introduction. Treatment of the oral cavity is an important problem of current oncology due to high morbidity and mortality reaching 43 % in 5-year period after diagnosis. frequency of positive resection margins is 30 % of cases which partially explains unsatisfactory results of therapy of this pathology and promotes investigation of methods increasing radicalness of surgical treatment of the primary lesion.The study objective is to evaluate the effectiveness of fluorescent visualization with 5-aminolevulinic acid for assessment of radicalness of surgical intervention in cancer of the oral mucosa.Materials and methods. In the study, evaluation of the effectiveness of 5-aminolevulinic acid for intraoperative determination of margins of squamous cell carcinoma of the oral mucosa (n = 36) was performed.Results. Comparison of intraoperative results using 5-aminolevulinic acid and results of histological examination showed that the difference in mean distances from the tumor edge to resection margin was 0.07 mm (95 % confidence interval 2.2905-2.4334) and wasn't statistically significant (p = 0.9519). Sensitivity of intraoperative fluorescent visualization with 5-aminolevulinic acid in diagnosis of resection margins was 100 %, specificity was 92.3 %, accuracy was 92.9 %, effectiveness was 96.1 %. Optimal effect of the fluorescent technique was achieved in patients with exophytic and mixed types of tumor growth without previous treatment.Conclusion. Method of intraoperative fluorescent visualization with 5-aminolevulinic acid showed high effectiveness (96.1 %) and can be recommended for intraoperative assessment of tumor margins and increase of radicalness of surgical treatment of cancer of the oral mucosa.